2020
DOI: 10.3390/rs12091478
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Clear-Sky Data Selection Algorithm for FY-3C/D Microwave Temperature Sounder-2

Abstract: The Fengyun (FY)-3C/D microwave temperature sounder-2 (MWTS-2) is similar to the Advanced Microwave Sounding Unit-A (AMSU-A), except it lacks two window channels located at 23.8 GHz and 31.4 GHz. This makes a clear-sky data determination challenging for the MWTS-2 due to the unavailability of cloud liquid water path (LWP) retrievable from the two window channels. The purpose of this study is to develop a clear-sky data selection algorithm for the FY-3C/D MWTS-2 based on the bias-removed differences between obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…fields. The value of O-B-μ(α)-μ(φ) is generally less (greater) than 2 K for AMSU-A channel 3 or MWTS channel 1 data with LWP less (greater) than 0.05 kg m -2 (see Figure 10 in Reference [41]). We can thus use…”
Section: Cloud Detection For Mwts Mwhs Hirad and Mwri Datamentioning
confidence: 98%
See 2 more Smart Citations
“…fields. The value of O-B-μ(α)-μ(φ) is generally less (greater) than 2 K for AMSU-A channel 3 or MWTS channel 1 data with LWP less (greater) than 0.05 kg m -2 (see Figure 10 in Reference [41]). We can thus use…”
Section: Cloud Detection For Mwts Mwhs Hirad and Mwri Datamentioning
confidence: 98%
“…A cloud detection algorithm was developed based on the FY-3 MWTS observations [40,41]. Firstly, these studies showed that cloud regions become distinguishable in the global distribution of are not dominated by the limb effect as O-B does for both AMSU-A channel 3 [40] and MWTS channel 1 [41], where μ ϕ ( ) and μ α ( ) are calculated using data collocated with AMSU-A clear-sky data points (LWP<0.01 g kg -1 ). Many of the cloud features seen in the LWP field are revealed in the…”
Section: Cloud Detection For Mwts Mwhs Hirad and Mwri Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The data of the FY series satellites used in the study were all downloaded from the Fengyun Satellite Data Center (http://satellite.nsmc.org.cn/portalsite/default.aspx), including the 1-h average thermal infrared radiation brightness temperature and visible wide-band albedo, and MWRI 36.5 GHz microwave radiation brightness temperature. For specific processing steps, refer to the relevant literature [25].…”
Section: Study Area and Observation Datamentioning
confidence: 99%
“…However, the FY-3D MWTS-2 lacks the two window channels at 23.8 and 31.4 GHz (see Table 1), which are critical for retrieving the cloud liquid water path (CLW) [10] and for cloud detection in the Gridpoint Statistical Interpolation (GSI) data assimilation system [11]. In previous studies, the cloud detection methods for the MWTS-2 were developed mainly by setting the cloud products from other instruments [12,13]. Recently, a convenient cloud detection method was proposed by Yang and Weng (2019) [14] that uses the brightness temperatures of 23.8 and 31.4 GHz channels reconstructed from a machine learning method.…”
Section: Introductionmentioning
confidence: 99%